ETHNIC DIVERSITY OF BANTENESE SOCIETY - Ayatullah Humaeni (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2017)
As an area that had ever been under the authority of Hindu Kingdom of Padjajaran in which the majority of its society professed Hindu and it had ever become one of the International trading centres and one of the central spots of Islamic studies in the archipelago during The Islamic Sultanate of Banten period in which many people of various ethnics came into Banten not only for conducting trading activities, but also for conducting religious proselytizing (dakwah) and studying Islam, Banten looked like becoming a magnet for people from many ethnics to earn a living, even to live permanently in Banten. Furthermore, they assimilated, integrated and conducted social interaction with local community of Banten. The majority of Bantenese society basically consisted of two dominant ethnics,